The mediating role of competitive and collaborative orientations in boosting entrepreneurial orientation's impact on firm performance - Rafał Kusa (Entrepreneurial Business and Economics Review (EBER), 2023)
Objective: This study aims to assess the role of the relationships between organizations in shaping entrepreneurial performance. In particular, I tested the mediating role of inter-organizational cooperation and competition in the relationship between entrepreneurial orientation and firm performance. Research Design & Methods: This quantitative study used structural equation modelling (SEM) to test hypotheses reflecting relationships among variables. I present the relationships in the research model. The research sample consisted of 117 one- and two-star hotels operating across Poland. Findings: The most original finding refers to the mediating role of relationships among organizations. In particular, the study unveiled the mediating role of both competitive and collaborative orientation in the relationship between entrepreneurial orientation (EO) and firm performance. In both cases mediation was partial. Thus, collaborative behaviours may be as important as competitive ones in transforming entrepreneurial approach into performance. Additionally, the findings confirm the positive impact of EO on competitive and collaborative orientation, as well as the positive impact of these three factors on firm performance. Implications & Recommendations: This study indicates that both entrepreneurs and researchers should consider inter-organizational relationships as a factor that can enhance entrepreneurial efforts. Thus, these relationships can play an important role in managerial practice and they can be a subject of research focused on organizational entrepreneurship. Regarding theory development, I recommend further studies on collaborative behaviours in pursuing and exploiting entrepreneurial opportunities; specifically, future studies can test presented relationships in other contexts (other industries, countries, and organization types). Moreover, I recommend the inclusion of other variables which can affect the tested relationships as they can help to explain the contingencies related to the tested model. Finally, further testing and improvement of used constructs (especially those reflecting cooperation and competition) are recommended. Contribution & Value Added: This study's findings contribute to the literature on entrepreneurship and inter-organizational relationships. Specifically, this study explains the role of two opposite postures, namely, cooperation and competition, in the context of entrepreneurial orientations. With its findings, the study augments our understanding of entrepreneurial posture and sheds new light on the operationalization of entrepreneurial orientation, which highlights the role of competing behaviours and omits collaborative actions.
Keywords: D22; L22; L25; L26; L83; 330; entrepreneurial orientation; inter-organizational cooperation; competition; performance; hotel; structural equation modelling (SEM)